Impact evaluation of biomedical waste segregation among junior residents of a South Indian medical college: a quasi experimental study - Sobagaiah, Ranganath T.; Patange, Karuna Siddappa; ., Vishwanatha (International Journal Of Community Medicine And Public Health, 2020)
Background: Biomedical waste is any waste generated during the diagnosis, treatment or immunization of human beings or animals. The quantity of solid waste generated in Bangalore hospitals is from ½ to 4 kg per bed per day. But segregation is done in only 30%. Health care workers have an important responsibility to segregate the biomedical waste and dispose them. Hence this study was undertaken with the objective of assessing the impact of intervention on Biomedical waste segregation knowledge among junior doctors. Methods: The study design employed is a quasi experimental study with control and intervention design. The junior doctors were selected randomly. After written informed consent the participants were divided as two group of intervention and control group with 74 in each group. Data of pre-test was collected using self-administered and validated questionnaire. After a week of pre-test, training using WHO modules 3 on training of biomedical waste segregation based on IHWM was done only for the intervention group. After a period of 3 months post test was conducted for both the intervention and the control group using a pre tested self-administered questionnaire with questions very similar to the pre-test. Results: The difference is found to be with t-test value of 1.434 and df of 37 with significant value 0.160 (>0.05) for the control group. The difference is found to be with t-test value of 3.241 and df of 35 with significant value 0.003 (<0.05) for the intervention group. Conclusions: The knowledge of biomedical waste management was found to increase after an intervention.